LRFD design and construction of shallow foundations for highway bridge structures - Paikowsky, Samuel G. (Transportation Research Board, 2010)
This report develops and calibrates procedures and modifies the AASHTO LRFD Bridge Design Specifications, Section 10-Foundations for the Strength Limit State Design of Shallow Foundations. The material in this report will be of immediate interest to bridge engineers and geotechnical engineers involved in the design of shallow foundations.
At head of title: National Cooperative Highway Research Program.
Keywords: Load factor design.; Bridges -- Foundations and piers -- Design and construction.; elektronické knihy; electronic books